2018
DOI: 10.1016/j.envint.2018.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Urinary concentrations and profiles of organophosphate and pyrethroid pesticide metabolites and phenoxyacid herbicides in populations in eight countries

Abstract: Concentrations of nine metabolites of organophosphate and pyrethroid insecticides, as well as two phenoxy herbicides, were determined in 322 urine samples collected from eight countries during 2006–2014 by high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS). The target pesticides were found ubiquitously, indicating widespread exposure of humans to pesticides in these countries. The highest sum concentrations of 11 pesticides were found in urine collected from Vietnam (median, 28.9 ng/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(36 citation statements)
references
References 41 publications
4
32
0
Order By: Relevance
“…Following statistical analysis, moderate to strong significant positive correlations were found between the volume‐based and the creatinine‐adjusted urinary concentrations of NNIs ( r = 0.244–0.837, p > 0.05; Supplemental Data, Table S1). This is suggestive that the concentrations of NNIs detected in the urine of the present study population were not influenced by urinary dilutions during the sampling process (thus, the impacts of urinary dilution factor on levels of NNIs in urine specimens from the present study subjects were minimal; Li and Kannan 2018, 2020). By running a correlation analysis (Supplemental Data, Table S2), the majority of the NNIs detected in the present study were found to show moderate to strong positive correlations among themselves ( r = 0.229–0.937, p > 0.05).…”
Section: Resultssupporting
confidence: 50%
“…Following statistical analysis, moderate to strong significant positive correlations were found between the volume‐based and the creatinine‐adjusted urinary concentrations of NNIs ( r = 0.244–0.837, p > 0.05; Supplemental Data, Table S1). This is suggestive that the concentrations of NNIs detected in the urine of the present study population were not influenced by urinary dilutions during the sampling process (thus, the impacts of urinary dilution factor on levels of NNIs in urine specimens from the present study subjects were minimal; Li and Kannan 2018, 2020). By running a correlation analysis (Supplemental Data, Table S2), the majority of the NNIs detected in the present study were found to show moderate to strong positive correlations among themselves ( r = 0.229–0.937, p > 0.05).…”
Section: Resultssupporting
confidence: 50%
“…We found that the concentrations of the metabolites in both TDID and S/H cohorts were comparable to NHANES 2009–2010 data. Nonetheless, according to a recent study the concentrations of pesticides tends to be lower in US in general compared to developing countries, such as India and Vietnam [ 70 ]. These differences in concentrations could be a result of policies to ban a number of pesticides, such as diazinon, or chlorpyrifos in the US [ 12 , 13 ], or different routes of exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Method details and quality control procedures for target analyte extraction have been previously described [ 36 ]. In brief, analytes were extracted using high-performance liquid chromatography (HPLC) and detected using tandem mass spectroscopy (MS/MS).…”
Section: Methodsmentioning
confidence: 99%
“…The analysis controlled for sample-to-sample carryover of target analytes, instrumental drift in response factors, and contamination in laboratory materials and solvents. The trace concentrations of target analytes found in procedural blanks were subtracted from those measured in urine samples [ 36 ]. Limits of detection (LODs) were 0.005 μg/L (4F-3-PBA); 0.007 μg/L (IMPY); 0.010 μg/L (TCPY, MDA, 3-PBA, trans -DCCA, cis -DCCA, 2,4-D); 0.025 μg/L (PNP); and 0.050 μg/L ( cis -DBCA, 2,4,5-T).…”
Section: Methodsmentioning
confidence: 99%